Decoloniality in Comics: an Afrofuturist vision of Contos dos Orixás - Forte Miranda Jr, Edmilson (2023)
Afrofuturism is proposed as a reading key to point out Contos dos Orixás, by Hugo Canuto as a decolonial expression. The publication assimilates a cultural element – the style of comic artist Jack Kirby – to draw the mythology of the orixás from a Brazilian perspective of Yorùbá culture. The methodology applies Simas’ and Rufino’s “cruzo” to articulate Afrofuturism, Design, and Cultural Studies in an analysis that deals with knowledge from what Grosfoguel understands as the subalternized side of the colonial difference. It is concluded that Yorùbá iconography was updated in the cruzo with Kirby’s futuristic design from Afro-Brazilian elements